The role of institutional quality in assessing the environmental externality of financial inclusion: A DCCE approach - Latif, Nazia; Safdar, Noreen; Liaquat, Malka; Younas, Kanwal; Nazeer, Nadia; Rafeeq, Rifat (Frontiers in Environmental Science, 2023)
Controlling environmental contamination requires the use of environmental regulation. The growth of green finance depends on digital finance. The objectives of the study are threefold. First to explore the impact of digital financial inclusion in deriving climate change. Second, to trace the shape of the financial inclusion-based environmental Kuznets curve. Third, investigate the intersecting effect of digital financial inclusion and institutional quality on environmental quality. Using panel data from 48 Asian economies between 1996 and 2020, Heterogeneity, non-stationarity, and cross-sectional dependence are addressed using an econometric method called "Dynamic Common Correlated Effects (DCCE)". The empirical evidence confirms a significant relationship between Environmental Performance and Financial Inclusiveness. Further, the findings also validated the inverted U shape environmental Kuznets curve based on financial inclusiveness. Our research suggests that a strong institutional framework has the potential to mitigate the long-term negative consequences of financial inclusion on the environment. To establish coordinated control of environmental quality, the government fully utilizes environmental regulation and digital inclusive finance environmental governance. Consequently, to achieve environmental sustainability, policymakers in Asian countries should develop policies that enhance financial inclusion and institutional quality.